TECHNOLOGY FOR IMPROVING SCIENCE TEACHING MECHANISMS - Aziza NORMUROTOVA (Scholar Express Journal, 2024)
These factors are the development of the educational system Reasonable conclusions about the need to change their approach or the actions being taken creates the need for release technologies. In this article, we consider the content of improving the mechanisms of teaching natural sciences, taking into account the above information .
Keywords: STEAM; PISA; TIMSS; integration